Optimization of Chitin Extraction and Conversion to Chitosan from Black Soldier Fly (Hermetia illucens) Pupae for Sustainable Biopolymer Production - Purwantiningsih Sugita; Muhammad Qurthubi Ash Shidiqqi; Kurniawanti Kurniawanti; Dewi Apri Astuti (Jurnal Kimia Sains dan Aplikasi, 2026)
Chitin and its derivative, chitosan, are natural polysaccharides with wide industrial applications due to their biodegradability and multifunctional biological activities. The black soldier fly (Hermetia illucens, BSF) represents a promising alternative source of chitin beyond conventional crustacean shells. However, studies on the optimization of chitin isolation from BSF pupae exuviae remain limited. This study aims to optimize the demineralization and deproteinization stages of chitin isolation and conversion to chitosan using a Box–Behnken design in Design-Expert 13. The effects of acid/base concentration, immersion time, and temperature were statistically evaluated to maximize chitin yield. The optimized conditions (3 M HCl, 1 M NaOH, 25°C, 1 h) resulted in a predicted chitin yield of 52.12%, which was experimentally validated to produce 50.83%. The isolated chitin had a low ash content (1.21%), indicating effective mineral removal and confirming its relatively high purity. The isolated chitin was subsequently deacetylated to chitosan, yielding 36% product with a degree of deacetylation (DD) of 53%. FTIR and XRD analyses confirmed the formation of partially deacetylated chitosan with a crystallinity index of 57%. It is concluded that the Box–Behnken optimization effectively enhanced process efficiency and enabled the systematic identification of optimal extraction conditions from BSF pupae shells, demonstrating their strong potential as a sustainable, non-crustacean source of chitin and chitosan for future biopolymer and green-material applications.